IMPLEMENTASI PERATURAN MAHKAMAH AGUNG REPUBLIK INDONESIA NOMOR 1 TAHUN 2016 TENTANG PROSEDUR MEDIASI DI PENGADILAN (Study Putusan Pengadilan Agama Rantauprapat No. No.487/Pdt.G/2020/PA-RAP Jo Putusan Pengadilan Tinggi Medan No.73/Pdt.G/2020/PTA-MDN) - Muhammad Yusuf Siregar (Universitas Labuhanbatu, 2020)
This study aims to analyze the legal aspects of the implementation of the Supreme Court Regulation No. 1 of 2016 on Mediation Procedures in Courts (Study of Rantauprapat Religious Court Decision No. 487 / Pdt.G / 2020 / PA-RAP Jo Medan High Court Decision No. 73 / Pdt.G / 2020 / PTA-MDN. This research is Normative Empirical, which is research by looking at conditions in the field by linking the source of laws and regulations in force in the Republic of Indonesia. The benefits that will be received from the results of this study are to find out and analyzing the legal position of the Supreme Court Regulation Number 1 of 2016 concerning Mediation Procedures in Courts and To find out and analyze the Implementation of the Supreme Court Regulation Number 1 of 2016 concerning Mediation Procedures in Courts in the Rantauprapat Religious Court Decision No.487 / Pdt .G / 2020 / PA-RAP Jo Medan High Court Decision No.73 / Pdt.G / 2020 / PTA-MDN. The results of the research show that the provisions of the Regulation of the Supreme Court of the Republic of Indonesia Number 1 of 2008 and / or Regulation of the Supreme Court of the Republic of Indonesia Number 1 of 2016 concerning Mediation Procedures in Courts in article 02 paragraph 04 states that